The Levels of Physician Disaster Preparedness Based on the Tsunami Vulnerability Zones in Banda Aceh - Taufik Suryadi; Balqis Qonita; Hafni Andayani; Agung Pranata (International Journal of Disaster Management, 2022)
Disasters caused by natural hazards may harm the health sector. It needs physician preparedness as a significant step in disaster risk reduction efforts and is expected to obtain an adequate response when a disaster occurs. This study aimed to determine the level of physician preparedness at the public health center (PHC) to face a tsunami caused by an earthquake based on the vulnerability zones. This research method is observational analytic with a cross-sectional design using a questionnaire developed by LIPI-UNESCO/ISDR adjusted to the core competencies and sub-competencies for disaster medicine and public health. The samples were collected in total sampling. The results show that most respondents have a preparedness index with categories almost prepare and not prepare, each of 12 respondents from a total of 42 people who participated in this study (28.56%). The physician from zone III has the best preparedness, and the physician from zone I are at least prepared for disasters. Statistical analysis using the Kruskal Wallis test obtained p-value 0.646 (p 0.05). The conclusion was found that there was no significant difference between the levels of physician preparedness at the PHC facing tsunami disasters based on the tsunami vulnerability zone in Banda Aceh.